Respuesta :
If your question is :
[tex] \frac{4}{7^3} [/tex]
Then the answer is:
[tex] \frac{4}{7*7*7} = \frac{4}{343} [/tex]
If your question is:
[tex] (\frac{4}{7}) ^{3}[/tex]
Then the answer is:
[tex] \frac{4*4*4}{7*7*7} = \frac{64}{343} [/tex]
[tex] \frac{4}{7^3} [/tex]
Then the answer is:
[tex] \frac{4}{7*7*7} = \frac{4}{343} [/tex]
If your question is:
[tex] (\frac{4}{7}) ^{3}[/tex]
Then the answer is:
[tex] \frac{4*4*4}{7*7*7} = \frac{64}{343} [/tex]
Answer:
[tex]\frac{64}{343}[/tex]
Step-by-step explanation:
The given expression is
[tex](\frac{4}{7})^3[/tex]
We need to find the simplified form of the given expression.
Using the distributive power property of exponent the given expression can be rewritten as
[tex](\frac{4}{7})^3=\frac{4^3}{7^3}[/tex] [tex][\because(\frac{a}{b})^x=\frac{a^x}{b^x}][/tex]
In can be written as
[tex](\frac{4}{7})^3=\frac{4\times 4\times 4}{7\times 7\times 7}[/tex]
On further simplification we get
[tex](\frac{4}{7})^3=\frac{64}{343}[/tex]
Therefore the simplified form of the given expression is [tex]\frac{64}{343}[/tex].